Competitiveness of Lemon Agroindustries within the Mexican Lemon Cluster in Colima, Mexico - Magaña Sánchez, Pablo Adrián (2010)
The present work refers to the study of the level of competitiveness of the Agribusiness lemon belonging to the cluster of Mexican lemon in Colima, Mexico, based upon the model of the IMD (International Institute for Management Development) and supporttheory. For this study there was a design of a measurement instrument according to the above model adapted to the context variables in our study. It should be mentioned that the IMD model was used to measure the competitiveness of countries. Thisresearch is generating a new tool that considers the research’s environment as that constituted by agribusiness enterprises of lemon in Colima, Mexico. this research focused on lemon.producing agroindustries. Furtherly, there was the determination of the level of competitiveness through statistical analysis and which variables or criteria were the ones significantly influencing such competitiveness.